A Comparison of the Effectiveness of Intensive Short-Term Psychodynamic Therapy and Emotion-Focused Therapy on Pain Self-Efficacy in Patients with Psychosomatic Disorders - Khanipoor Kakesh , Parisa; Keykhosrovani, Moloud; Mousavi, Seyed Asghar (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to compare the effectiveness of Intensive Short-Term Psychodynamic Therapy and Emotion-Focused Therapy on pain self-efficacy among patients diagnosed with psychosomatic disorders.Methods and Materials: This applied study employed a quasi-experimental pretest–posttest design with a control group and a three-month follow-up period. The statistical population consisted of patients with psychosomatic disorders who referred to Niayesh Psychiatric Hospital in Tehran between July 2024 and March 2025. Forty-five participants meeting inclusion criteria were selected through purposive sampling and randomly assigned to three groups: Intensive Short-Term Psychodynamic Therapy, Emotion-Focused Therapy, and a control group (15 participants in each group). The experimental groups received structured therapeutic interventions across weekly sessions, while the control group remained on a waiting list without treatment. Data were collected using the Takata and Sakata Psychosomatic Complaint Scale and the Pain Self-Efficacy Questionnaire. Data analysis was conducted using SPSS-28 at descriptive and inferential levels, including analysis of covariance, mixed analysis of variance, repeated-measures ANOVA, and Bonferroni post hoc tests.Findings: Analysis of covariance indicated that both Intensive Short-Term Psychodynamic Therapy (p = 0.008) and Emotion-Focused Therapy (p < 0.001) significantly improved pain self-efficacy compared with the control group, with Emotion-Focused Therapy demonstrating a larger effect size. Repeated-measures analysis revealed a significant effect of time (p < 0.001) and a significant interaction between time and group (p < 0.001), confirming differential change patterns across interventions. Bonferroni post hoc comparisons showed that both experimental groups had significantly higher adjusted posttest scores than the control group, while no significant difference was observed between the two treatment approaches. Pairwise comparisons demonstrated significant improvements from pretest to posttest and from pretest to follow-up in both intervention groups, with no significant decline between posttest and follow-up, indicating stability of treatment effects.Conclusion: Both Intensive Short-Term Psychodynamic Therapy and Emotion-Focused Therapy were effective in enhancing pain self-efficacy among patients with psychosomatic disorders, and the improvements remained stable over time, suggesting that emotion-oriented psychological interventions can play a significant role in strengthening adaptive coping and psychological functioning in psychosomatic populations.